PENGARUH KONSENTRASI TEPUNG MAIZENA TERHADAP KUALITAS FISIK SUSU KAMBING GORENG - Rizki Rizki; Metha Monica; Fatati Fatati (PT. Hasba Edukasi Mandiri, 2026)
This study aimed to determine the effect of adding cornstarch at different concentrations on the physical quality of fried milk, including pH, moisture content, and yield. The research was conducted at the Laboratory of the Faculty of Animal Science, Universitas Jambi, on March 20–21, 2025, using an experimental method with a Completely Randomized Design (CRD) consisting of four treatments and five replications, namely P0 (0%), P1 (5%), P2 (10%), and P3 (15%) based on milk weight. The production process involved heating the milk, adding cornstarch, stirring until thickened, molding, cooling, and frying. Data were collected through pH measurement using a pH meter, determination of moisture content using the thermogravimetric method, and yield calculation based on the ratio of final product weight to initial material weight. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test if significant effects were observed. The results showed that the addition of cornstarch significantly affected pH, moisture content, and yield (p < 0.05). The pH value decreased from 6.59 in P0 to 6.44 in P3, while the moisture content increased from 16.93% to 29.81%. The highest yield was observed in P1 (11.95%) and decreased in P3 (10.48%). Based on these results, it can be concluded that the addition of cornstarch significantly affects the physical quality of fried milk, and a 15% concentration is recommended to achieve a better texture.